ENT 530 Social Media Portfolio: Young Living By Hazlyana / Siti Hazlyana Mohamad Khairi - Mohamad Khairi, Siti Hazlyana (2021)
Young Living is the business that sell various of plant based essential oil and diffuser. The scents of the essential oil can make the customers fall in love with our essential oil. I started this business because there are not lot of people sells diffuser and essential oil in Malaysia. This business I started in April 2021. The Young Living name come up as we used essential oil that are plant based which give a lot of benefit and lead you a healthy lifestyle. A healthy lifestyle means that we will live our life as how we should live when we were young. The purpose of running this business is to promote the benefit of using plant based essential oil that people rarely use in their everyday life. As we maintained the quality of the product with a suitable price, our target market is basically a whole family. A father, mother, children or even grandparents. This can give everyone the chance to gain benefits of the essential oil. So far, Young Living has launched two types of products. First one is the diffuser with a different design but same function and the second one is 10 types of different scents and benefits of essential oil. These two products work well together as the essential oil need to be diffuse all around the house. The best way to use our essential oil is to diffuse it around the house so everyone can gain the benefits.